Assessing the Coverage of Biofortified Foods: Development and Testing of Methods and Indicators in Musanze, Rwanda. Current Developments in Nutrition - Petry, N.; Wirth, J.P.; Friesen, V.M.; Rohner, F.; Nkundineza, A.; Chanzu, E.; Tadesse, K.G.; Gahutu, J.B.; Neufeld, Lynnette M.; Birol, Ekin; Boy, Erick; Mudyahoto, Bho; et al. (Elsevier, 2020)
Background: Biofortification of staple crops has the potential to increase nutrient intakes and improve health outcomes. Despite program data on the number of farming households reached with and growing biofortified crops, information on the coverage of biofortified foods in the general population is often lacking. Such information is needed to ascertain potential for impact and identify bottlenecks to parts of the impact pathway.